Numerical Analysis of a Two-Phase Flow (Oil and Gas) in a Horizontal Separator used in Petroleum Projects - Yayla, S.; Kamal, K.; Bayraktar, S. (ISFAHAN UNIV TECHNOLOGY, 2019)
In the present paper, two-phase three-dimensional turbulent flow simulations are carried out by applying computational fluid dynamics (CFD) technique to the internal flow of a horizontal separator that is used in petroleum industry. Two different geometries are considered; the separator with a straight plate at the top and the separator with the straight plate on the side of the separator. Effects of the location, distance between the inlet of the separator and the diverter plate and inlet velocity on the separation efficiency are investigated by employing the standard k- epsilon turbulence model. For these purposes, three different distances between the straight diverter plate and the inlet to the separator (0.1 m, 0.15 m and 0.2 m) and four different velocities (0.25 m/s, 0.5 m/s, 0.75 m/s, and 1 m/s) are taken into account by means of Euler mixture model. It is revealed that the maximum separation efficiency is 99.772% when the mixture enters the separator from the top with the inlet velocity of 0.25 m/s and the plate is located 0.2 m away from the inlet section of the separator. An inverse correlation is detected between the inlet velocity and the efficiency of the separation since increasing the inlet velocity decreases the efficiency of the separation.
Keywords: Computational fluid dynamics (CFD); Horizontal separator; Two phase flow; Phase separation; Thermodynamics; Mechanics